Carbon-rich compounds: from molecules to materials - Haley, Michael M.; Tykwinski, Rik R. (Wiley-VCH, 2006)
This is the only up-to-date book on the market to focus on the synthesis of these compounds in this particularly suitable way. A team of excellent international authors guarantees high-quality content, covering such topics as monodisperse carbon-rich oligomers, molecular electronic wires, polyaromatic hydrocarbons, nonconjugated small molecules, nanotubes, fullerenes, polyynes, macrocycles, dendrimers, phenylenes and diamondoid structures. The result is a must-have for everyone working in this expanding and interdisciplinary field, including organic and polymer chemists, materials scientists